Flash flood and submergence management with Sub-1 variety with direct seeding in Côte d'Ivoire - CGIAR Research Program on Rice (2019)
This technology has been evaluated in three consecutive seasons in Bouake (Africa Rice Center) and with all three seasons promising results, seeds of these two varieties have been distributed for the participatory variety selection (PVS) in Bouake and Gagnoa (CI) with alternative establishment method (wet-direct seeding method of crop establishment).